What's Worth Knowing? Economists' Opinions about Economics - Armin Falk; Peter Andre (Center for Economic Studies and ifo Institute (CESifo), 2021)
We document economists' opinions about what is worth knowing and ask (i) which research objectives economic research should embrace and (ii) which topics it should study. Almost 10,000 economic researchers from all fields and ranks of the profession participated in our global survey. Detailed bibliometric data show that our sample represents the population of economic researchers who publish in English. We report three main findings. First, economists' opinions are vastly heterogeneous. Second, most researchers are dissatisfied with the status quo, in terms of both research topics and objectives. Third, on average, respondents think that economic research should become more policy-relevant, multidisciplinary, risky and disruptive, and pursue more diverse topics. We also find that dissatisfaction with the status quo is more prevalent among female scholars and associated with lower job satisfaction and higher stress levels. Taken together, the results suggest that economics as a field does not appreciate and work on what economists collectively prefer.
Keywords: A11; A14; 330